Pengaruh Corporate Social Responsibility Pada Manajemen Laba - Ardiani, Ni Luh Nia; Sudana, I Putu (E-Jurnal Akuntansi; Vol 24 No 3 (2018)DO - 10.24843/EJA.2018.v24.i03.p26, 2018)
This study aims to determine the effect of corporate social responsibility on earnings management with good corporate governance as a moderating variable in high profile companies listed on the Indonesia Stock Exchange in year 2014-2016. Data is obtained through the official website of the Indonesia Stock Exchange. Sampel of 33 observation is obtained with purposive sampling method. Data collection method using documentation method. Data are analyzed using moderation regression analysis. This study concludes that corporate social responsibility has a negative effect on earnings management, institutional ownership and the audit committee moderate the effect of corporate social responsibility on earnings management. Managerial ownership doesn’t moderate the effect of corporate social responsibility on earnings management. Political cost theory states that high political costs will tend to provide opportunities for earnings management. The results of this study aren’t agree with the political cost theory. The results of this study provide an argument that broad disclosure of corporate social responsibility isn’t always followed by earnings management practices. Keyword : corporate social responsibility, earning management, institusional ownership, managerial ownership, audit committee